´´ Diseño e Implementación de un sistema electrónico de tipo d.i.s (sistema de encendido directo) utilizando un módulo programable para mejorar el rendimiento de un vehículo suzuki modelo forsa año 1989´´ - López López, Stalin Jesús (2023)
The present technological proposal consisted of the design and implementation of an electronic ignition system type D.I.S (Direct Ignition System) a programmable module was used to improve the performance of an engine in idle mode of a Suzuki Forsa model year 1989'' already that said engine had several factors that decreased its performance causing damage to the engine, excessive fuel consumption, therefore with the bibliographical research and the field research carried out, the area of application of the technological proposal was determined in which the replacement of mechanical components with electronic ones, which improved engine performance in idle mode thereby optimizing fuel consumption by 80.65% compared to the conventional system that was installed, considering the reduction of expenses both in fuel purchase .